Investigation of Saline Water Intrusion in the Borazjan Freshwater Aquifer from the Dalaki and Helleh Rivers - J. Mozafarizadeh; Z. Sajadi (مهندسی منابع آب, 2013)
Freshwater scarcity in the Borazjan Plain is approaching a crisis state.  Helleh and Dalaki, as two of the most important surface water resources, are claimed to be the main source of salt pollution of the local Borazjan aquifer.  To validate this claim, and to develop strategies to mitigate this disturbing process, water samples were obtained from 22 representative production wells scattered on the plain, and from the Helleh River. Results of the chemical analyses of these samples were correlated with their positions relative to the geological formations and other potential sources of contamination. Results indicated that both the Dalaki and Helleh Rivers   were instrumental in the water quality deterioration. Furthermore, dissolution of halite and gypsum from the geological formations that abound in the area contribute NaCl and CaSO4 as the main contaminants of the aquifer; the discarded brine from the oil wells and the irrigation return flow contribute to water pollution as well. The distinct linear trend between Na and Cl concentrations in the ionic ratio diagram indicated the mixing of fresh and saline water, and an occurrence of surface water intrusion, especially in the central and northwest of the plain. However, recharge from limestone formations in the eastern part of the plain improves the water quality in that area. Over-pumping tends to increase the thickness of the fresh-saline water mixing zone, thus increasing the   salinity of production wells' salinity. Prudent management of groundwater is a practical policy in sustaining the use of this limited precious resource in the Borazjan Plain.